2020
DOI: 10.24189/ncr.2020.041
|View full text |Cite
|
Sign up to set email alerts
|

Oswaldocruzia filiformis sensu lato (Nematoda: Molineidae) from amphibians and reptiles in European Russia: morphological and molecular data

Abstract: Nematodes of the genus Oswaldocruzia parasitise the small intestine of amphibians and reptiles. Their biodiversity remains unknown. We studied Oswaldocruzia nematodes from nine species of amphibians and reptiles (Pelophylax ridibundus, Rana arvalis, Rana temporaria, Bufo bufo, Lacerta agilis, Zootoca vivipara, Anguis fragilis, Natrix natrix, Vipera berus) at six localities in European Russia in 2018-2019. To identify their nematode species, we analysed the morphological characters traditionally used in the tax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 30 publications
3
18
0
Order By: Relevance
“…Waterbody size did affect helminth abundances but not their species richness in our study. The nematode O. filiformis is also common in sand lizards (Lacerta agilis) from dry terrestrial habitats (Kirillova et al, 2020). It infects hosts through ingestion of its larvae with terrestrial food (Chikhlyaev et al, 2019b) and its higher infection rates in frogs from smaller waterbodies could be caused by higher proportions of terrestrial prey items in such habitats (relevant studies on waterbody-size-specificity of their diets are absent).…”
mentioning
confidence: 99%
“…Waterbody size did affect helminth abundances but not their species richness in our study. The nematode O. filiformis is also common in sand lizards (Lacerta agilis) from dry terrestrial habitats (Kirillova et al, 2020). It infects hosts through ingestion of its larvae with terrestrial food (Chikhlyaev et al, 2019b) and its higher infection rates in frogs from smaller waterbodies could be caused by higher proportions of terrestrial prey items in such habitats (relevant studies on waterbody-size-specificity of their diets are absent).…”
mentioning
confidence: 99%
“…Distribution: Palaearctic. The results of partial sequencing and molecular phylogenetic analysis of CoxI mtDNA gene showed that all Oswaldocruzia species in this study belonged to the same species [119].…”
Section: Family Trichostrongylidae Leiper 1908mentioning
confidence: 63%
“…Furthermore, phylogenetic approaches to representatives of Molineidae are limited since they include few species or are focused only on certain genera (De Bellocq et al 2001;Chilton et al 2006;Kirillova et al 2023). In relation to Oswaldocruzia, the situation may be considered more critical because only five out of 90 species have been genetically characterised, namely, O. belenensis Santos, Giese, Maldonado & Lanfredi, 2008, O. chabaudi Ben Slimane & Durette-Desset, 1996, O. chambrieri Ben Slimane & Durette-Desset, 1993, and O. filiformis and O. ukrainae Ivanitzky, 1940, in addition to several sequences labelled as Oswaldocruzia sp., in which makers for cox1 are by far the most common (see Willkens et al 2016;Kirillova et al 2020Kirillova et al , 2023. Therefore, the currently limited genetic evidence does not allow further conclusions about the phylogeny of Oswaldocruzia.…”
Section: Discussionmentioning
confidence: 99%
“…2016; Kirillova et al . 2020, 2023). Therefore, the currently limited genetic evidence does not allow further conclusions about the phylogeny of Oswaldocruzia.…”
Section: Discussionmentioning
confidence: 99%